KEANEKARAGAMAN SEMUT PREDATOR ARBOREAL (HYMENOPTERA FORMICIDAE) DI PERKEBUNAN KELAPA SAWIT SPPN SEMBAWA BANYUASIN - Falahudin, Irham; Rizal, Syamsul; Dahlia, Dahlia (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2011)
ABSTRACTResearch on the diversity of predatory arboreal ants (Hymenoptera:Formicidae) in oil palm plantations SPPN Sembawa Banyuasin conducted in September to October 2010. This research used the temple of traps. Identification results of research conducted at the Laboratory Department of Biology Faculty of Mathematics and Science University of PGRI Palembang and the Faculty Tarbiyah State Islamic Institute Raden Fatah Palembang. The results obtained by 349 individuals, consisting of 7 species, 5 genera, and 3 subfamilia. Species that have a relative density and the highest relative frequency of either catching the morning andlate afternoon is Oeccophylla sp 1. Diversity of predatory arboreal ants index gained on oil palm plantations in the capture of the morning was 1.054, while the afternoon was 1.038. Community similarity index gained 83%, predatory arboreal ants community showed 83% caught in the morning, also caught in the afternoon.Key words: diversity, ants predatory, arboreal, community similarity